2015
DOI: 10.3109/21678421.2015.1030430
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Edinburgh Cognitive and Behavioural Amyotrophic Lateral Sclerosis Screen (ECAS): A cognitive tool for motor disorders

Abstract: Our objective was to assess the validity of the Edinburgh Cognitive and Behaviour ALS Screen (ECAS), a multi-domain screen designed to detect cognitive deficits in patients with motor disorders. Forty ALS patients (without pre-diagnosed dementia) and 40, age-, gender- and education-matched healthy controls were recruited. All participants underwent extensive neuropsychological assessment and the ECAS. Performance at neuropsychological assessment across five domains (fluency, executive function, language, memor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
119
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 19 publications
11
119
0
Order By: Relevance
“…Cut-off scores, based on 2 standard deviations (SD) below the mean, for abnormality have previously been reported for the ECAS-A (14) and validated against a full neuropsychological battery (17). The present study demonstrated that the newly presented alternate versions are highly equivalent to the original ECAS.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Cut-off scores, based on 2 standard deviations (SD) below the mean, for abnormality have previously been reported for the ECAS-A (14) and validated against a full neuropsychological battery (17). The present study demonstrated that the newly presented alternate versions are highly equivalent to the original ECAS.…”
Section: Discussionsupporting
confidence: 61%
“…Not only has the ECAS shown high sensitivity and specificity to cognitive impairment against a full neuropsychological battery (17)(18)(19)(20)(21), it has high clinical utility in describing the nature of these impairments. Monitoring progression of cognitive and behavioural symptoms may have important implications for patient management, treatment, prognosis, end-oflife decision making, and caregiver burden (22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore a variety of simple tools have been used to screen for cognitive impairment in ALS. These include Addenbrooke's cognitive examination-III (ACE-III), an updated version of the ACE-R [5][6][7][8], the Frontal assessment battery (FAB) [9][10][11], the Edinburgh cognitive and behavioral ALS screen (ECAS), which includes tests of social cognition, [12][13][14][15][16] and the ALS cognitive behavioral screen (ALS CBS) [17]. Table 1 shows the elements tested in the different tools.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Moreover, studies have shown that individuals with ALS present cognitive impairment, regardless of the type of neuropsychological assessment performed [22] [23] [24] [25]. Understanding cognitive impairment in ALS could provide more information about the pathogenesis of neurodegeneration and inform patient care [3] [26] [27] [28].…”
mentioning
confidence: 99%